Tafsir Teoretis Asas Fundamental Merdeka Belajar - Karim, Bisyri Abdul; Syahid, Akhmad (Education and Learning Journal, 2021)
This paper examines the independence of learning which is the focus of advancing national education today. In the author's analysis, at least the big title â€œfree learningâ€ contains the complexity of the meaning of liberating the learning process which has been constrained by the system itself. There are three important things in the explanation of the Minister of National Education regarding freedom of learning, namely freedom of innovation, independent learning and creative learning. The author assumes these three things as the fundamental principles of the free learning policy. The three fundamental principles cannot be separated from the theoretical basis. Based on the results of the theoretical analysis carried out, it can be stated that the freedom of innovation will encourage teachers and students to be free without restraint to carry out various experiments to try new things to produce renewable ideas. Independent learning provides opportunities for students to choose to study to explore certain academic skills by formulating the motives of goals to be achieved according to their academic abilities.Â